2017
DOI: 10.1111/1751-7915.13029
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy, biodistribution and safety of an inhibinDNAvaccine delivered by attenuatedSalmonella choleraesuis

Abstract: Summary DNA vaccines, the third‐generation vaccines, were extensively studied. The attenuated Salmonella choleraesuis (S. choleraesuis) was widely focused as a carrier to deliver DNA vaccines in the chromosome–plasmid balanced‐lethal system. The efficacy of inhibin DNA vaccine delivered by attenuated S. choleraesuis was proved in mice and cows in our previous studies. In this study, the efficacy of inhibin DNA vaccine was confirmed in rhesus monkeys. To further study the biodistribution and safety, the mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, the idea of using inhibin immunity to increase animal fertility is emerging. Chen et al revealed that active immunization of rhesus monkeys with an inhibin DNA vaccine increases their IgA and IgG antibody titers, which is an effective method to induce ovulation in primates and promote the reproduction of endangered rhesus monkeys (Chen et al, 2018). Inhibin immunity can not only promote the development of follicles but also induce superovulation in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the idea of using inhibin immunity to increase animal fertility is emerging. Chen et al revealed that active immunization of rhesus monkeys with an inhibin DNA vaccine increases their IgA and IgG antibody titers, which is an effective method to induce ovulation in primates and promote the reproduction of endangered rhesus monkeys (Chen et al, 2018). Inhibin immunity can not only promote the development of follicles but also induce superovulation in animals.…”
Section: Discussionmentioning
confidence: 99%
“…For oral administration of DNA, non-pathogenic ( L. lactis [ 221 ] or attenuated ( S. thyphimurium [ 222 ] and L. monocytogenes [ 223 ]) bacterial strains are often used as vectors, termed bactofection [ 224 ]. In the intestine, these bacteria may be phagocytosed directly by mucosal DC/macrophages spreading extensions into the gut lumen or after M cell-mediated transcytosis at the Peyer’s patches [ 225 ].…”
Section: Route Of Vaccinationmentioning
confidence: 99%